Klebsiella pneumoniae Orbital Cellulitis: Clinical Manifestations and Outcomes in a Tertiary Medical Center in Taiwan - Chieh-Hung Yen; Shu-Ya Wu; Yi-Lin Liao (Journal of Ophthalmology)
Purpose. To report six cases of Klebsiella pneumoniae orbital cellulitis without preceding endophthalmitis. Method. Retrospective chart review. Results. We reported four females and two males admitted to our hospital for Klebsiella pneumoniae orbital cellulitis proven by computed tomographies and bacterial cultures from May 1995 to March 2017. Proptosis, conjunctival congestion, and chemosis and limitation of ocular motility were present in all six patients. Four patients had decreased visual acuities, and three of them recovered completely after treatment. The origin of the infection was sinus in four patients, skin wound in one patient, and sepsis presumably caused by a dental procedure in one patient. Three of all six patients had underlying diabetes mellitus. Two patients had orbital cellulitis before they were diagnosed of diabetes during hospital stay. Conclusion. Diabetes may be a risk factor of Klebsiella pneumoniae orbital cellulitis, especially for those of nonsinus origin.